Enhancing critical thinking and soft skills in generation z psychology students through project-based learning: Evidence from a board game intervention - Ifa Hanifah Misbach; Maryama, Hanna; Farhan Zakariyya; Gemala Nurendah (Universitas Ahmad Dahlan, 2026)
Generation Z students are characterized by impatience, fear of missing out (FOMO), low tolerance for conventional learning methods, and difficulties in collaboration during conflict situations. This study aims to implement a Project-Based Learning (PjBL) design for first-semester Psychology students at UPI in the History and Schools of Psychology course, with the goal of enhancing critical thinking through Higher-Order Thinking Skills (HOTS) and developing soft skills. The research employed a mixed methodology combining action research with a single-group pretest–posttest experimental design. Students were tasked with creating board games based on psychological theorists. Evaluation and reflection were conducted periodically by both instructors and students, with instructors providing three formal review sessions. Results indicate that PjBL significantly improves HOTS, leading to enhanced learning outcomes. Statistical analysis revealed significant differences (p < .001) across Review 1, Review 2, and Final Review scores. Qualitative coding of student reflections further demonstrated notable improvements in soft skills, particularly in managing personal and group conflicts. These findings suggest that PjBL is an effective pedagogical strategy for fostering critical thinking and collaborative competencies among Generation Z learners.